The Role of Nahwu and Sharf Sciences in Arabic Language Learning - Ismi Nujaima; Hendra Kurniawan (Jurnal Al-Hibru, 2024)
Language is a tool for thinking, expressing and communicating. One of the basic competency development areas in kindergarten is language development. Language allows children to translate experiences into symbols that they can use to communicate and think. The study of sharaf or Arabic morphology is about word forms. In Arabic, syntax is known as nahwu. Sharif (2017:97) says, "Syntax is the study of the relationship between words, phrases, clauses, and sentences with other words, phrases, clauses, and sentences". So learning Nahwu is learning the rules of phrase arrangement in sentences. Morphology is a branch of linguistics that identifies the basic units of language and studies the intricacies of word forms and the effect of word changes on the meaning of parts of speech. In Arabic linguistics, the term morphology is known as sharaf. The word sharaf itself means word transformation that results in a change in word form, which results in a change in meaning, and the word transformation is known as At-Tashrif. The results of the At-Thasrif process produce wazan or scales which then become the standard for Arabic word formation. Arabic morphology has emerged as an independent discipline from the linguistics of the parent Arabic language. The author uses qualitative research methods, namely with literature studies or in other languages called literature studies. Literature study or literature study is part of a scientific work which contains a discussion of previous research and also from scientific references that are relevant to the research that the author describes in the work that the author wrote.